The Effect of Oral Contraceptive Estrogen on Blood Coagulation and Fibrinolysis - Hedlin, Anne M (Thrombosis and Haemostasis, 1975)
The changes in fibrinogen, antithrombin activity, spontaneous fibrinolytic activity, plasminogen and fibrinogen degradation products were studied in women, aged 18 to 30 years, who were using oral contraceptive preparations. Blood samples were obtained before use, as well as during the first month and again after several months of use. The results were divided into three groups based on the antiovulatory activity of the estrogen component of the oral contraceptive, ie. Mestranol, 50 μg, Mestranol 80 μg or Ethinyl estradiol 50 μg and Mestranol 100 μg. In each of the three groups there was a similar pattern of increase in spontaneous fibrinolytic activity and plasminogen but decrease in antithrombin levels during the monthly cycles. The fibrinogen level was increased in the first month of oral contraceptive use in the three groups but after several months of use the pattern of change seen in the first month was repeated with the lower estrogen compounds, but in the group using the preparation with 100 μg Mestranol, the fibrinogen level returned to that of the control month. The level of fibrinogen degradation products remained unchanged.